Anti-HBs Positivity Related to Past HBV Infection and Vaccination in Older Adults in Polish Population—Cohort-Based Study - Katarzyna Zięba; Kacper Jagiełło; Joanna Musialik; Łukasz Wierucki; Adam Hajduk; Małgorzata Mossakowska; Jerzy Chudek (Vaccines)
Background: In Poland, a national hepatitis B (HBV) immunization program was introduced for neonates in 1996, and between 2000 and 2011, those born from 1986 to 1995 were vaccinated. Little is known about vaccination rates among adults born before 1986. This study aimed to determine the frequency of anti-HBs seropositivity rates related to vaccination and past HBV infection in older Poles. Methods: The HBV serological status was analyzed in 5781 (96.6%) of the PolSenior2 population-based cohort (60+) by assessing serum seropositivity for HBs antigen, anti-HBs, and anti-HBc antibodies. The survey was performed in 2018–2019 and included medical and socio-economic questionnaires, anthropometric measurements, and comprehensive geriatric assessment. Results: Serological status implying past hepatitis B and serological profile consistent with anti-HBV vaccination corresponded to 15.2% (95% CI: 13.4–17.0) and 25.2% (95% CI: 23.4–27.0) prevalences, respectively. Female gender, living in a town or city, having better education, and suffering from coronary artery disease, or depression independently increased the rate of past hepatitis B. On the other hand, being ‘white collar’ and self-reliant, having the ability to use the Internet, and past surgical procedures in the last 5-year period were factors associated with a higher vaccination rate. Conclusions: More than 15% of older adults in Poland present serological profiles suggesting past hepatitis B, and one-fourth anti-HBV vaccination. Being functionally independent, ‘white collar’, using the Internet, and having past surgical procedures are factors associated with a higher chance of being vaccinated. Nevertheless, a large group of older adults should be prophylactically vaccinated due to increased exposure to medical procedures.